(3EOGQI GdJShjb GdSjGMj (B/s - (3GdMOjO, GHQGgje GSeGYjds ((3YeGf(B: s (3OGQ GdGYUGQ(B, s, 2010)
(3eaGgje h JWhQ GdJShjb,EOGQI GdJShjb h GdGWGQ GdfXQj fXGe h HjFI GdJShjb , GdJShjb GdSjGMj , GdeSJgdc GdSjGMj , GdYQV h GdWdH GdSjGMj , JShjb GdGYeGd , GdJNWjW h GdJfHD aj GdJShjb , eaghe GdGSJQGJjLjI GdJShjbjI , GSJQGJjLjGJ GdefJLGJ , GdGSJKeGQaj GdJWhjQ (B.s
(3eQGLY U(B.289s
Keywords: (3COGQI GdeHjYGJs; (3GdJShjbs; (3GdJShjb(B- (3GdSjGMIs; (3GdSjGMIs; (3UfGYI GdSjGMIs